Cardinal Montini´s Religious Project, on the avant-garde of Milanese architecture. The study case of Mater Misericordiae, an icon of modernity - Gómez Gómez, María Belén (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2017)
During the 50s’ the city of Milan experienced a fast growth to accommodate the population that arrived into the city as a consequence of the migratory movements that took place at the end of the Second World War. Some organizations, such as the Archbishopric of the city, tried to provide with spiritual help to the inhabitants of this developing areas. This initiative turned into a plan for the construction of new parish churches in the settlements around the city. In the year 1955 Giovanni Battista Montini - who a few years later would become pope Paulus VI- Became archbishop of Milan and took over the management and planning for the construction of new churches. He was responsible for the modern image of sacred architecture in this city. Montini commissioned a group of innovative architects with proven experience that had already worked in Milan or other parts of Italy to deliver some of the Projects. At the same time, he appointed a group of young architects with relatively little experience in the field of ecclesiastical architecture and put them in charge of a second group of projects projects. Under Montini the rhythm of churches construction in the neighborhoods around Milan increased considerably and more than one hundred churches were constructed during this period and the following years. This paper discusses the contribution of the Diocese of Milan, within the renovation of the church as an institution through its architecture, to define the identity of some of the new peripheral areas of the city. For this purpose, some of the most interesting examples of architecture constructed during this period have been selected. Among all this constructions the church of Mater Misericordiae can be singled out for a number of reasons. These new sacred constructions became symbols of the important Liturgical renewal that had started a few decades before in some other parts of Europe. Some of these new architectural proposals, in which the Catholic Church tried to reconcile modern and sacred art, became new models of reference in which tradition and modernity went hand by hand. In the case of the church of Mater Misericordiae a high level of experimentation, well above some other contemporary sacred and civil constructions, can be recognized. This is an evidence of Montini’s commitment, to support a really avant-garde renewal project.
Keywords: Post-war Milan; Sacred architecture; Liturgical renewal; Church and modernity